Investigação do mecanismo de degradação e da participação de agentes sequestrantes na fotocatálise com TiO2/UV do corante índigo carmina - Gomes Neto, Jéssica Santos (2018)
In dye waste water, the color produced by small amounts of organic dyes in water is a big concern because color in water is aesthetically unpleasant and can affect aquatic plants due to reduced transmission of sunlight through water.This work evaluates the optimal degradation conditions of indigo carmineby heterogeneous photocatalytic degradation with TiO2 and ultraviolet light (UV), one of the most effective advanced oxidative processes (AOPs) for removal of contaminants from air and water. From the optimal condition, the degradation pathway of compounds investigated, using scavenger of hole (KI), hydroxyl radical (2-propanol and tert-butanol) and singlet oxygen (Na3N). In high concentrations of KI, there was color removal, but no reduction of aromatic compounds was observed at the end of the photocatalytic degradation. In addition, reduction of rates of color removal occurred only in presence of hole scavenger. The results suggest that indigo carmine degradation is occurring through oxidation in the vacancy formed on the catalyst surface.